Efektivitas Dakwah Fi’ah: Studi Model Dakwah pada Lembaga Dakwah Kampus - Asep Iwan Setiawan (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2011)
Campus Da’wah Institution (CDI) is a movement who which done by student especially in giving members comprehension about their religious behavior. One of destination, to increase comprehension about their religion throught mentoring that done each Monday, so the members become trained and consistence in achieving their destination, with it’s indicator such as: ritual involving, ideology, intellectual, experience and consequencial.